The Impact of Standardized Infectious Diseases Consultation on Postsplenectomy Care and Outcomes. (30th July 2022) - Hale, Andrew J; Depo, Benjamin; Khan, Sundas; Whitman, Timothy J; Bullis, Sean; Singh, Devika; Peterson, Katherine; Hyson, Peter; Catoe, Laura; Tompkins, Bradley J; Alston, W Kemper; Dejace, Jean
Abstract: Background: Patients who receive splenectomy are at risk for overwhelming postsplenectomy infection (OPSI). Guidelines recommend that adult asplenic patients receive a complement of vaccinations, education on the risks of OPSI, and on-demand antibiotics. However, prior literature suggests that a majority of patients who have had a splenectomy receive incomplete asplenic patient care and thus remain at increased risk. This study assessed the impact of standardized involvement of infectious diseases (ID) providers on asplenic patient care outcomes in patients undergoing splenectomy. Methods: A quasi-experimental study design compared a prospective cohort of patients undergoing splenectomy from August 2017 to June 2021 who received standardized ID involvement in care of the asplenic patient with a historic control cohort of patients undergoing splenectomy at the same institution from January 2010 through July 2017 who did not. There were 11 components of asplenic patient care defined as primary outcomes. Secondary outcomes included the occurrence of OPSI, death, and death from OPSI. Results: Fifty patients were included in the prospective intervention cohort and 128 in the historic control cohort. There were significant improvements in 9 of the 11 primary outcomes in the intervention arm as compared with the historic controls. Survival analysis showed no statistically significant difference in the incidence of OPSI-free survival between the groups ( P = .056), though there was a trend toward improvement in the prospective intervention arm. Conclusions: Standardized involvement of an ID provider in the care of patients undergoing splenectomy improves asplenic patient care outcomes. Routine involvement of ID in this setting may be warranted.